Second Generation Patient Specific Total Knees Demonstrate a Higher Manipulation Rate Compared with “Off-the-shelf” Implants - Haeder, Paul R.; Chong, Alexander C.M.; Bhargava, Tarum (Kansas Journal of Medicine, 2019)
Introduction. Patient specific total knee arthroplasty (TKA) theoretically provides a more accurate fit to the native knee but may have difficulty achieving full range of motion (ROM) post-operatively. Post-operative ROM data were compared between patients who underwent cemented patient-specific cruciate-retaining (PSCR) and standard cemented posterior-stabilized (SPS) TKAs. Methods. PSCR and SPS TKAs that were performed from January 2014 to September 2015 by the same surgeon using the same postoperative protocols at two selected facilities were reviewed. Twoand six-week post-operative ROM data were obtained and the number of patients with knee flexion less than 110° was recorded. Results. Twenty-one patients in the PSCR group and 57 patients in the SPS group were included. The percentage of patients with knee flexion less than 110° was similar in both groups preoperatively (10% vs 14%, p = 0.60) and two-week post-operatively (57% vs 68%, p = 0.35). However, at six-week post-operatively there was significant difference (29% vs 7%, p = 0.01). Conclusions. These results provide evidence to alert orthopaedic surgeons when using these patient specific implants versus conventional TKA methods. Patients whose TKA was performed using patient specific cutting guides struggled to obtain 110° of knee flexion. Close monitoring, aggressive physical therapy, and early manipulation are recommended when using patient specific cutting guides and custom total knee implants. Further evaluation in a larger group of patients is warranted. KS J Med 2016;9(4):88-92.